Evaluation of dental expertise with intra-oral peri-apical view radiographs for forensic identification - Kanwalpreet Bhullar; Ramandeep Bhullar; Sundaresan Balagopal; Arathi Ganesh; Mathan Rajan (Journal of Forensic Dental Sciences, 2014)
Background: Identification of a dead person is important in starting the investigation into the circumstances of death. In the absence of forensic odontologist, it is vital that general dentists are able to compare the ante mortem-post mortem (AM-PM) records and with their ability, correctly interpret the individuality of the person. Aims: This study wascarried out to find out the accuracy with which undergraduate, graduate and post-graduate dentists can do this comparison, using the simulated AM-PM intra-oral peri-apical (IOPA) view radiographs. Setting and Design: A total of 60 investigators of which 20 undergraduate students, 20 general dentists, 20 post-graduate dentists viewed 10 pairs of simulated AM and PM radiographs and recorded their findings. Materials and Methods: Ten pairs of simulated AM-PM IOPA view radiographs were given to 60 dentists to investigate their discriminatory potential for dental identification purposes. The results were statistically analyzed. Statistical Analysis: χ2 -test and Mann-Whitney U-test were carried out to compare the sensitivity, specificity and accuracy of the three types of examiners (UG, G, PG). Results: The results showed sensitivity of 59.8%, specificity of 62.6%, accuracy of 61% for undergraduate students, sensitivity of 86.6%, specificity of 87.5%, accuracy of 87% for graduate doctors, sensitivity of 89.3%, specificity of 92.3% and accuracy of 90.5% for post-graduate doctors respectively. Conclusion: Inexperienced investigators in forensic identification showed fairly acceptable results, therefore, introduction of forensic odontology in an undergraduate course may help general dentists to provide better service, if required, in the absence of a forensic odontologist.